Potentialities in Creating the Pedestrian Malls in the Historical City Centers : A Study Case of Mawlawi Street, Sulaimani, Iraqi Kurdistan - Ismael, Karzan Saleem; Mohammed, Najmaldin Hussien; Rasul, Hoshyar Qadir (Kurdistan Journal of Applied Research, 2019)
The characteristics of public open spaces in the city center play an important role in attracting people to walk when they attend their daily needs, entertainment and interact with other physical and even nonphysical feature of the built environment. The notion of car-free streets or pedestrian malls, especially in the downtown or the historical city centers has been emerged as a critical challenge faced to whose are responsible for urban managing, besides of urban planner and architects as well. Many factors (outside and inside) contribute to take the decision in transforming these streets into the pedestrian malls. Sulaimani as the other historic cities, although has the most compacted and traditional structure, especially in original and commercial part of the city, has suffered from the congested city center which day by day increases, the related urban problems and became more un-friendly. The study will identify the considerations that promote the decision makers in order to transform the most significant street in the historical city center into a pedestrian mall. This aim requires to investigate factors which have become more common in most studies conducted previously, but some factors which were considered as effective and invisible at the same time, will act potentially and has been more impressive in enhancing these types of decisions. Mixed methods have been used for analyzing the case study. The results displayed that the Mawlawi street has the potentiality in transforming to a pedestrian mall. In conclusion, the decisions and some possible solutions have been introduced for awareness of city?s authorities in order to take place in their near future development programs.